Consultations for HIV post-exposure prophylaxis before and after health insurance coverage of pre-exposure prophylaxis to a university-based emergency department in Germany - Lennert Böhm; Björn-Erik Ole Jensen; Hubert Schelzig; Tom Luedde; Michael Bernhard (HIV Research & Clinical Practice)
Background: Potential risk contacts for HIV transmission may lead to presentations to the emergency department (ED) for counseling and initiation of post-exposure prophylaxis (PEP). Objective: To examine the impact of German health insurance covering pre-exposure prophylaxis (PrEP) following Sept 1st 2019 for certain risk groups on the frequency and reasons for PEP counseling in a university-based ED in Germany. Methods: In a before-after study design, all persons aged ≥18 years who presented for PEP counseling were analyzed retrospectively. We compared characteristics of presentations in the 18 months prior to PrEP coverage on Sept 1st, 2019, with those in the following 18 months. Results: 154 ED presentations occurred in the first study period, and 155 ED presentations in the second period. Regarding the reasons for ED visits, no statistically significant difference was found [occupational risk contact (18.2 vs. 26.5%, p = 0.081), sexual risk contact (74.7 vs. 69.0%, p = 0.266), other non-occupational risk contact (7.1 vs. 4.5%, p = 0.329)]. For men who have sex with men (MSM), no statistically significant differences were found [38.9 (n = 60) vs. 35.5% (n = 55), p = 0.537]. All persons presenting to the HIV outpatient clinic after ED PEP initiation (n = 60 vs. n = 52) tested negative for HIV 3 months later. Conclusion: In this study, reasons to present for PEP counseling to a university ED showed no change following the implementation of PrEP coverage by health insurances. Therefore, PEP remains an important prevention for HIV transmission and presentations to the ED for PEP counseling may provide an opportunity to educate persons at risk of HIV infection about PrEP, thereby helping to prevent new HIV infections.